Models of Churn Probabilities of Clients of Financial Institutions - Houšková, Helena; Černý, Michal; Formánek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
The aim of this thesis is to create models that will predict the probability of client churn during mortgage refixation from a year to six months in advance using three different methods. Separate models are made for the clients who applied for the loan directly in the bank and for those that applied through a broker. The reason is different churn rate in these two groups as well as possibility tu use additional variables for the second group of clients. The used methods are logistic regression, regression tree and random forest. Models are compared with each other as well as with the model that is currently used in the bank. To compare the models the Gini coefficient and the confusion matrix are used. For both groups of clients, the best model is the random forest, which has the highest Gini coefficient on the test sample.
Vedoucí práce: Michal Černý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses